Music and Tiktok in Social Sciences: A Didactics of Brain Languages - De Moya Martínez, María del Valle; Segura Tornero, Alfredo; González Amo, Gema (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Advances in neuroscience and cognition are key to addressing contemporary educational challenges. The study introduces a novel intervention through TikTok in 5th grade, using an interdisciplinary approach based on the 'languages of the brain'. It incorporates participatory learning, music integration and a natural language approach that includes choreography and video creation. Using quantitative and qualitative methods with 101 students, the results show a positive impact on the understanding of content about the Middle Ages. They highlight the effectiveness of this approach in improving student engagement in today's interdisciplinary education.